TEACHER’S DIGITAL COMPETENCE IN THE EUROPEAN EDUCATIONAL DISCOURSE - Stoika, Olesia (The Modern Higher Education Review, 2023)
This article highlights the key principles of forming a teacher’s digital competence. The purpose of the article is to highlight the peculiarities of forming a teacher’s digital competence, taking into account European approaches to this process. During the problem formulation process, a combination of interdisciplinary methods is employed: theoretical methods such as analysis and synthesis to identify the main directions of research into the digital transformation of teacher education; empirical methods, including the study of scientific works and legislative framework related to the digitization of teacher education, and so on. The documents that cover the issues of forming digital competence in students, in particular future teachers, are considered. It has been found that in the European context, teacher training in digital skills should be based on the principles of digital citizenship. This means a critical approach to information that allows educators to navigate the digital world and develop an understanding of the core values of democracy. Studies have shown that the development of teachers’ digital skills can be enhanced by gaining the ability to use digital technologies to improve the quality of teaching, educational development, and personal and continuous professional development. It has been established that modern teachers can use digital technologies to effectively managе and organize the educational process, which significantly expands the capabilities of students, taking into account their abilities, needs and interests. Therefore, mastery of digital technologies will ensure an effective, inclusive and innovative learning environment for students.